2007
DOI: 10.1007/s10071-007-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for route integration and strategic planning in wild capuchin monkeys

Abstract: Both in captivity and the wild, primates are found to travel mostly to the nearest available resource, but they may skip over the closest resource and travel to more distant resources, which are often found to be more productive. This study examines the tradeoff between distance and reward in the foraging choices of one group of wild capuchin monkeys (Cebus apella nigritus) using feeding platforms in large-scale foraging experiments conducted over four years. Three feeding sites were arrayed in an oblique tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 53 publications
7
88
0
14
Order By: Relevance
“…In an experimental Weld study, Janson (1998) found that capuchins were willing to travel further for more productive sites. Janson (2007) presents experimental data that shows that capuchins will skip a smaller resource if visiting the smaller site adds too much travel time to reaching a larger site. Cunningham and Janson (2007) present observational data indicating that the travel path of saki monkeys is determined by highly productive trees.…”
Section: What-where-how Much and Whenmentioning
confidence: 99%
See 2 more Smart Citations
“…In an experimental Weld study, Janson (1998) found that capuchins were willing to travel further for more productive sites. Janson (2007) presents experimental data that shows that capuchins will skip a smaller resource if visiting the smaller site adds too much travel time to reaching a larger site. Cunningham and Janson (2007) present observational data indicating that the travel path of saki monkeys is determined by highly productive trees.…”
Section: What-where-how Much and Whenmentioning
confidence: 99%
“…Valero and Byrne (2007), Cunningham and Janson (2007) and Janson (2007) look at the information that monkeys integrate when deciding on a foraging path. Valero and Byrne's analysis of the foraging routes of their study subjects, suggest that the spider monkeys plan their routes more than one step at a time.…”
Section: The Papers In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, most observational and experimental Weld studies of spatial memory (e.g. Boesch and Boesch 1984;Garber 1988Garber , 1989Garber and Dolins 1996;Garber and Hannon 1993;Garber and Paciulli 1997;Janson 1996Janson , 1998Janson , 2007Menzel 1991;Noser and Byrne 2007;Pochron 2001;Robinson 1986;Sigg and Stolba 1981;Valero and Byrne 2007) and experimental captive studies (e.g. Gallistel and Cramer 1996;MacDonald and Wilkie 1990;Menzel 1973;Menzel 1999;Tinklepaugh 1932) have focused on primates which, in nature, inhabit large home ranges with widely dispersed resources.…”
Section: Introductionmentioning
confidence: 99%
“…It is less obvious whether in situations of high food-patch density, reliance on spatial memory is necessary (Janson 1996). Even when food patches are common, primates might rely on spatial memory to travel to highly productive or preferred resources, rejecting less productive but closer resources (Garber 1989;Janson 1998Janson , 2007. Conversely, certain trees might be avoided because they are distasteful (e.g.…”
Section: Introductionmentioning
confidence: 99%